1996
DOI: 10.1530/eje.0.1340639
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of thyroid cell proliferation by epidermal growth factor is different from cell growth induced by thyrotropin or insulin-like growth factor I

Abstract: Isolated intact porcine thyroid follicles free of contaminating single cells were embedded in "Matrigel", which is a gel-forming basement membrane preparation containing mainly collagen type IV, laminin, heparan sulfate proteoglycans and entactin. Follicles were treated with different growth factors: thyrotropin (TSH), insulin-like growth factor I (IGF-I), epidermal growth factor (EGF) or transforming growth factor beta. Cell proliferation was quantified by counting cell numbers. Morphological studies were don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…The decreased slope in transgenic mice suggests that there may be an impaired response of thyroid follicle cells to TSH, with regard to thyroid hormone synthesis. This is consistent with previous reports that IGF-I plays a facilitatory role in TSHinduced thyroid hormone synthesis (3,32).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The decreased slope in transgenic mice suggests that there may be an impaired response of thyroid follicle cells to TSH, with regard to thyroid hormone synthesis. This is consistent with previous reports that IGF-I plays a facilitatory role in TSHinduced thyroid hormone synthesis (3,32).…”
Section: Discussionsupporting
confidence: 94%
“…However, the relative increase in RTW following goitrogen treatment compared with the untreated group was less pronounced in transgenic mice than in wild-type mice, despite the difference in TSH levels. This supports the concept that IGF-I is involved in TSH-mediated growth (3,32) and that the overexpression of IGFBP-1 in transgenic mice impairs TSH action (27,33). Serum levels of T 3 and T 4 were decreased in transgenic, compared with wild-type mice.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As reported by Bechtner et al (1996), many in vitro studies investigating thyroid cell function and growth have been carried out on single cells. However, these authors argue that the follicle organization of thyroid cells is important for the maintenance of polarization, speci®c functions and the regulation of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be possible that IGF may affect thyroid cells, and play a role in the development of thyroidal diseases. Studies have revealed that this molecule facilitates thyroid epithelium proliferation, induced by thyroid stimulating hormone in animal studies (9,10). Increased expression of IGF-1 receptors has been documented in thyroid tissue in patients with Graves' disease and thyroid cancer (11,12), and the relationship between the tissue and serum levels of IGF-1 and the development of multinodular goiter has also been shown (13,14).…”
Section: Introductionmentioning
confidence: 99%